2007
DOI: 10.1370/afm.723
|View full text |Cite
|
Sign up to set email alerts
|

HPV and Cervical Cancer Prevention Counseling With Younger Adolescents: Implications for Primary Care

Abstract: PURPOSE Primary care clinicians will continue to play an important role in cervical cancer prevention, particularly with regard to administration of the newly licensed human papillomavirus (HPV) vaccine and continued administration of Papanicolaou tests. Little is known about the factors that infl uence cervical cancer prevention counseling, particularly in the adolescent encounter. We conducted a qualitative study to better understand the implications for counseling about cervical cancer prevention by primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
2
45
1
1
Order By: Relevance
“…17,22,27,29,35,38,40,76,81 Second, at the interpersonal level, many providers perceived parents as being unsupportive of HPV vaccination, a view which hindered guideline-consistent delivery of recommendations. 12,29,33,35,[37][38][39] Third, studies consistently documented a challenging policy context, including unclear practice guidelines and a lack of school entry requirements for HPV vaccination. 11,27,34,59,74 Finally, participants across several studies perceived clinical systems as unconducive to communication due to factors such as time constraints and deficiencies in reminder/recall systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,22,27,29,35,38,40,76,81 Second, at the interpersonal level, many providers perceived parents as being unsupportive of HPV vaccination, a view which hindered guideline-consistent delivery of recommendations. 12,29,33,35,[37][38][39] Third, studies consistently documented a challenging policy context, including unclear practice guidelines and a lack of school entry requirements for HPV vaccination. 11,27,34,59,74 Finally, participants across several studies perceived clinical systems as unconducive to communication due to factors such as time constraints and deficiencies in reminder/recall systems.…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies of providers with higher participation in Medicaid or the Vaccines for Children program found that this participation was associated with more positive HPV vaccine recommendation practices 9,23,30,[33][34][35] or no effect. 29,44,48 Provider recommendations did not vary substantially by national region, 30,[33][34][35]39,44 but providers practicing in urban areas more often reported recommending HPV vaccine than those in rural or suburban ones. 34,37,44,46 Audience Variation in recommendations by patient factors Studies assessing patient factors associated with receiving an HPV vaccine recommendation most often examined patient demographics and providers' perceptions of patients' risk of HPV infection.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 96%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16][17][18] Although vaccination intent was increased, it was neither sustained nor translated into vaccination behavior. Furthermore, there has been speculation that parents from different ethnic and socioeconomic groups may face different barriers to vaccination and thus require different intervention strategies, 17,19 a critical point in the context of disparate HPV disease outcomes.…”
mentioning
confidence: 99%